A PHONOLOGICAL STUDY OF CONSONANT PHONEMES ON NGANJUK JAVANESE DIALECT - YULI NUGRAHENY (1996)
Language is a means of connecting and identifying of each individual to interact to each other. Language can be used to indicate the background of some one. Dialects may show people's original region. There are phenomena on Nganjuk Javanese dialect, especially in the phonology field. These phenomena of phonology can differentciate Nganjuk Javanese dialect from other Javanese dialects. Because of telecommunication sophisticated technology, the youngsters in Nganjuk begin to leave Nganjuk Javanese dialect when they communicate among themselves. If this condition continues, it is not imposible if Nganjuk Javanese dialect will disappear. For that reason stock taking of Nganjuk Javanese dialect is needed to safe this dialect. This research is expected to be one of the ways to solve this problem. The population that are intended to be taken as informants for this research are people in Kabupaten Nganjuk from three kecamatans. They are Kecamatan Loceret, Kecamatan Rejoso and Kecamatan Bukomoro.